2020
DOI: 10.1111/jnc.15214
|View full text |Cite|
|
Sign up to set email alerts
|

Mislocalisation of TDP‐43 to the cytoplasm causes cortical hyperexcitability and reduced excitatory neurotransmission in the motor cortex

Abstract: Title: Amyotrophic lateral sclerosis associated mislocalisation of TDP-43 to the cytoplasm causes cortical hyperexcitability and reduced excitatory neurotransmission in the motor cortex.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 71 publications
5
54
0
Order By: Relevance
“…The most likely disease profile of an ALS patient is no known genetic mutation, focal motor cortex hyperexcitability which has the propensity to cause widespread network dysfunction and TDP-43 protein which is excluded from the motor neuron nucleus [10,19]. How these critical disease profiles interact is only starting to be comprehended [13,20] and how these changes result ultimately in neuronal demise remains an important research question. Therefore, we endeavoured to interrogate whether TDP-43 mislocalization contributes to the generation of upper motor neuron dysfunction through altering neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The most likely disease profile of an ALS patient is no known genetic mutation, focal motor cortex hyperexcitability which has the propensity to cause widespread network dysfunction and TDP-43 protein which is excluded from the motor neuron nucleus [10,19]. How these critical disease profiles interact is only starting to be comprehended [13,20] and how these changes result ultimately in neuronal demise remains an important research question. Therefore, we endeavoured to interrogate whether TDP-43 mislocalization contributes to the generation of upper motor neuron dysfunction through altering neuronal circuitry.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous Thy1-YFP transgenic mice (B6.Cg-Tg(Thy1-YFP)HJrs/J/ Stock No: 003782) [28,29] were crossed with previously described Camk2α-tTa (B6;CBA-Tg(Camk2a-tTA)1Mmay/Stock No: 003010). Mice heterozygous for Thy1-YFP and Camk2α-tTa were bred with tetO-TDP-43∆NLS (B6;C3-Tg(tetO-TARDBP*)4Vle/J/Stock No: 014650) and tetO-TDP-43 WT mice (B6;C3-Tg(tetO-TARDBP)12Vle/J/Stock No: 016841) [20,27]. These strains have inducible expression of TDP-43 with the removal of doxycycline from their diet.…”
Section: Mouse Cohortmentioning
confidence: 99%
See 2 more Smart Citations
“…Muscle weakness and rigidity, CFS, exhaustion, and sleep disorders (e.g., insomnia, REM sleep behavior disorder) are the most common chronic symptoms observed in patients post-COVID-19recovery [14]. There has not been sufficient time to study and understand the long-term impacts and implications of COVID-19 in depth since the beginning of the pandemic; however, recent studies have identified substantial and long-term adverse health effects.…”
Section: Introductionmentioning
confidence: 99%